Gambaran pengetahuan dan sikap mahasiswa kedokteran gigi di indonesia mengenai OPMD (Laporan Penelitian) - Evita Dewi Fortuna; Firstine Kelsi Hartanto (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Oral cancer in Indonesia still has a fairly high prevalence. The appearance of oral cancer can be initiated by the presence of Oral Potentially Malignant Disorder (OPMD) lesions, which is a disorder that may become a malignancy with a condition that is often preceded by the development of cancer of the lips and oral cavity. The knowledge and attitudes of dental education students regarding OPMD need to be achieved well so that it can be applied when practicing as a dentist. Objective: To describe the knowledge and attitudes of dental students in Indonesia regarding Oral Potentially Malignant Disorder. Method: This is a descriptive observational study with a cross-sectional design. The research was conducted by distributing an online questionnaire through a google form consisting of 47 questions about knowledge and attitudes to 211 clinical dental students faculty of dentistry in Indonesia. Respondents are classified into three levels based on their responses to the questionnaire, such as high, medium, and low. Results: A total of 211 respondents were 83.4% female and 16.6% male, of whom were aged ≤ 21 years old (16.6%), 22 – 24 years old (60.2%) and ≥ 25 years old (23.2%). A total of 125 subjects (59.2%) had high knowledge category and 86 subjects (40.8%) had a moderate category. Meanwhile, 195 subjects (92.4%) had attitudes in the good category, 13 subjects (6.2%) in the moderate category and 3 subjects (1.4%) in the poor category. Conclusion: The knowledge of OPMD among dental students in Indonesia were high with scores of 18.45 + 0.21, whereas the attitudes were good with scores of 17.10 + 0.17.